Metaverse-Based Evacuation Training: Design, Implementation, and Experiment Focusing on Earthquake Evacuation - Hiroyuki Mitsuhara (Multimodal Technologies and Interaction)
Virtual reality (VR) can realize evacuation training in an immersive, interactive, safe, three-dimensional virtual world. Many VR-based evacuation training systems have been developed; however, they typically notify participants explicitly or implicitly before the evacuation training; thus, participants are mentally ready for successful evacuation. To satisfy a prerequisite where participants do not have mental readiness, this study proposes a prototype of a metaverse-based evacuation training system called “Metavearthquake”. The main characteristic of the proposed prototype system is that evacuation training begins unexpectedly due to a sudden earthquake in the metaverse (virtual world); participants are then required to evacuate to a safe place while making decisions under difficult earthquake-caused situations. The prototype system introduces scenarios and nonplayable characters to express difficult situations that may occur after an earthquake occurrence. To heighten training effects, the prototype system supports reflection (reflection-on-action) by replaying the evacuation of participants. An experiment implied that a sudden earthquake is indispensable for realistic simulated evacuation experiences. In summary, Metavearthquake is a metaverse-based evacuation training system that provides realistic simulated earthquake evacuation experiences in terms of evacuation behaviors, emotions, and training effects.